Balancing Weight Loss and Sarcopenia in Elderly Patients With Peripheral Artery Disease - Damianos G. Kokkinidis; Ehrin J. Armstrong; Jay Giri (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
See Article Polonsky et al